RSV-CLASS - Clinical Assessment Severity Score: an easy-to-use clinical disease severity score for respiratory syncytial virus infection in hospitalized children - Gsenger, Julia; Bruckner, Thomas; Ihling, Clara Marlene; Rehbein, Rebecca M.; Schnee, Sarah Valerie; Hoos, Johannes; Manuel, Britta; Pfeil, Johannes; Schnitzler, Paul; Tabatabai, Julia (Journal of medical virology, 2023)
Respiratory syncytial virus (RSV) is the most common cause of acute respiratory tract infection in infants and young children often leading to severe disease requiring hospitalization. However, validated tools for systematic assessment of disease severity are lacking. This study aimed at creating and validating a standardized, simple-to-use disease severity score for RSV infection in children—the RSV-CLASS (Clinical Assessment Severity Score). Therefore, data from over 700 RSV-infected children over six winter seasons (2014-2020) was analyzed using univariate and multiple regression analyses for the prediction of lower respiratory tract infection (LRTI) as a proxy for a severe course of the disease. Testing a broad range of respiratory symptoms, they eventually yielded seven items. Performing stepwise selection, these were reduced to the final four items: cough, tachypnea, rales, and wheezing, each receiving one point in the proposed score named RSV-CLASS. The score was calculated for children in two cohorts A and B, one for development and one for validation, with an area under the curve of 0.90 and 0.87, respectively. With a score value of 3 or 4, 97.8% and 100% of the children, respectively, were admitted with LRTI and classified correctly. The RSV-CLASS is a disease severity score based on a neutral, analytical approach using prospective data from a large study cohort. It will contribute to systematically assessing the disease severity of RSV infection and can be used for evidence-based clinical decision-making as well as for research settings.
Online veröffentlicht: 12. Februar 2023
Gesehen am 05.10.2023